Establishment of ELISA method for canine adenovirus type 1 - Wang, Ben; Xu, Jinfeng; Zhang, Hui; Lian, Shizhen; Duan, Yichang; Zhang, Hongling; Hou, Wei; Yin, Baishuang; Zhu, Yanzhu (Frontiers in Veterinary Science, 2024)
Canine adenovirus (CAdV) had a high prevalence in fox populations and induced fox encephalitis. No ELISA kits specifically for CAdV-1 antigen had been commercialized for foxes in China. It is crucial to develop a rapid and accurate ELISA method for detecting of CAdV-1. The monoclonal antibodies (mAbs, IgG1A) and HRP-labeled polyclonal antibodies (pAbs) were used to establish the ELISA method in this experiment. The results showed that the optimal concentration and coating time for the mAbs (IgG1A) were 2.15 μg/mL and overnight at 4°C, respectively. The dilution ratio of the HRP-labeled pAbs was 1:2000. Five percent skimmed milk was selected as the blocking agent. The optimal incubation times for blocking, CAdV-1, and HRP-labeled pAbs were all 1 h. The cut-off value for negative rectal swab was determined to be 0.366 ± 0.032. The maximum dilution ratio was 100 TCID50/mL. The ELISA method was positive to CAdV-1, and that was negative to CAdV-2, Canine Parvovirus (CPV) and Canine Distempervirus (CDV). The ELISA method showed good repeatability, sensitivity, and specificity. Compared with RT-PCR, the sensitivity, specificity, and coincidence rates of the ELISA method were 93.75, 90.9, and 92.86%, respectively. These results indicate that the established ELISA method can be used for the large-scale screening and epidemiology surveillance of CAdV-1 in foxes.